Kuala Kedah towards a heritage tourism destination: A preliminary perspective - Ahmad, Mohamad Zaki; Ibrahim, Johan Afendi; Zakaria, Norria; Mohd Salleh, Hood (2009)
At present heritage is generally an important aspect for many tourists.In many parts of the world, heritage is categorized and recognized as one of the vital components of tourism development especially when it is linked to tourism and recreational activities.Nowadays, there is increasing evidence that traveling to a destination rich- in- heritage is gaining more popularity and becoming a growing trend. Due to greater potential of heritage-based tourism all over the world Kuala Kedah, which is known as a fishermen village and very synonymous to the history of Kedah's Sultanate, should take the opportunity to be developed as a destination for heritage tourism.Therefore, this conceptual paper will unwrap and explain aspects such as definition and concept of heritage, heritage tourism, dynamic interaction between tourism and sustainability and threat of tourism to cultural heritage before discussing some potentials and opportunities in developing Kuala Kedah as an attractive and successful destination for heritage tourism.At the end of this paper, some recommendations will be proposed to help Kuala Kedah plan and develop a more efficient and ideal tourism.